Legal aspects of protecting the Ukrainian population against emergencies under martial law - O. A. Lukianykhina; S. A. Petrovska (Bulletin of Kharkiv National University of Internal Affairs)
It is emphasized that the place of the hostilities consequences (the use of certain types of weapons against the civilian population) in the emergency system is a new problem for the world scientific thought. It is important to understand these consequences, in particular within the context of building a fair and proper legal status at the legislative level for those categories of workers involved in overcoming the consequences of such emergencies, not only employees of the SES and the police, but also of critical infrastructure, transport, healthcare, and trade.